Tari Lenggang Cisadane: Representasi Kearifan Lokal dalam Dinamika Budaya Tangerang - Muhammad Arif Wicaksono; Eko Ribawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine how the Cisadane Lenggang Dance can be a representation of local wisdom in the cultural dynamics of Tangerang City. This research uses a qualitative research method of literature study by collecting various sources and references related to the topic to be studied and interpreting from the sources that have been collected. From the results of the study, it was found that the Cisadane Lenggang Dance is a dance that has the meaning of a welcome dance or as a dance to welcome every guest who comes and visits the city of Tangerang. This dance was created by an artist and cultural expert named H. Unus Ahmad Sanusi in 2008. This dance is a form of local wisdom that is characteristic for the residents of Tangerang City because it represents cultural diversity and describes harmony in the life of a multi-ethnic, multi-cultural community and has hospitality and politeness between people in Tangerang City.